Pendampingan Legalitas Usaha dan Produk UMKM Anggota BMT NU Singgahan - Moh.Muhajir; Lukman Khoirin; Sugito (Warta LPM, 2023)
Individuals or groups that produce products, be it food, goods or services, don't just sell without a product identity. As a form of identity for the product that is owned, a brand is needed to provide the identity of the product. The identity of the product can be in the form of a product brand and the legality of the product. In this study, assistance is provided to MSME actors for product legality. Assistance is carried out with the target of BMT NU Singgahan members who have businesses. The assistance was carried out with the first step, namely a business survey owned by BMT NU Singgahan members who are MSME actors. Furthermore, the focus group discussion (FGD). After the FGD, it will be followed by socialization of the mentoring program that will be carried out. In addition to outreach, this study provides training on how to obtain product legality in the form of business registration numbers (NIB), home industry food production certificates (SPP-IRT), halal certificates, and brands registered with the Directorate General of Intellectual Property (DJKI) as well as product financing by BMT NU Singgahan. The resource persons in the training were from the Tuban Health Office, Curator of Curation Houses, Companion for Halal Solution Institute (PPH LSH) ISNU Tuban halal products, and BMT NU Singgahan. From the results of a study that has been conducted, there are 24 MSMEs from 8 villages partnering with BMT NU Singgahan who are willing to be assisted in submitting the legality of MSME products and businesses including NIB, SPP-IRT, halal certificates, and brands registered with the Directorate General of Intellectual Property (DJKI) as well as product financing by BMT NU Singgahan.